Erysipelas on port-wine stain. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
There are no report in Pubmed talking about an association between erysipelas and port-wine stain. Erysipelas is a superficial, acute cellulitis, usually caused by Group A beta-hemolytic streptococcus (GABHS). It is observed also in the normal children due to the presence of a concomitant skin wound. However, GABHS and skin wounds are much more frequent than erysipelas. The latter thus requires other favoring factors. Among the latter there are excess weight, venous insufficiency, lymphedema, diabetes, immune deficiency, nephrotic syndrome (1, 3) and port-wine stain as our case suggests. Some Authors (2) showed that in subjects with recurrent erysipelas of a limb there is a defective lymphatic drainage also in the non affected limb.